COMPARATIVE ANALYSIS OF GROWTH PARAMETERS AND CULTIVATION OF THE SACCHAROMYCES CEREVISIAE S288C YEAST STRAIN IN VARIOUS MEDIA (International Conference on Modern Science and Scientific Studies, 2025)
The aim of the study is to investigate the optimal conditions for the cultivation and proliferation of the yeast strain Saccharomyces cerevisiae S288c.